Critical CALL – Proceedings of the 2015 EUROCALL Conference, Padova, Italy 2015
DOI: 10.14705/rpnet.2015.000343
|View full text |Cite
|
Sign up to set email alerts
|

An EFL flipped learning course design: utilizing students’ mobile online devices

Abstract: This paper reports on a research project in a university English as Foreign Language (EFL) program in Japan which explored ways to sustain active participation in e-learning tasks. The tasks were intended to improve students' scores on the Test of English for International Communication (TOEIC), a test used by businesses to make hiring decisions. The research adopted a Flipped Learning (FL) approach to Blended Learning (BL). A web-based courseware, ATR CALL BRIX (http://www.atr-lt.jp/products/brix/index.html),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
(1 reference statement)
0
4
0
Order By: Relevance
“…Chen Hsieh et al (2017) also had students draft ‘the final dialog collaboratively’ (p. 4) under the conventional learning condition. Hung (2015) and Ishikawa et al (2015) likewise had their non-flipped learning groups engage in classroom discussions about the content presented in class. While not all researchers intentionally used communicative activities for their comparison groups, the fact that communicative features were observed in both the flipped and non-flipped groups makes it unlikely that the results of the present meta-analysis are attributable simply to communicative activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chen Hsieh et al (2017) also had students draft ‘the final dialog collaboratively’ (p. 4) under the conventional learning condition. Hung (2015) and Ishikawa et al (2015) likewise had their non-flipped learning groups engage in classroom discussions about the content presented in class. While not all researchers intentionally used communicative activities for their comparison groups, the fact that communicative features were observed in both the flipped and non-flipped groups makes it unlikely that the results of the present meta-analysis are attributable simply to communicative activities.…”
Section: Discussionmentioning
confidence: 99%
“…Intermediate was anchored to B1 according to the CERF. As an illustration, Ishikawa et al (2015) was coded as ‘below intermediate’ as the reported TOEIC scores were within the A2 range of 250 to 550; Karimi and Hamzavi (2017) was coded as intermediate since reported Cambridge PET scores established a B1 level. The remaining studies were coded in the same manner where either empirical evidence or an argument anchoring the learners’ proficiency (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fewer studies have been conducted at the primary and secondary school levels (Unal & Unal, 2017;Yang, 2017). The researchers in EFL mostly explored the use of the FCM in general academic success in second language learning (Ishikawa et al, 2015;Unal & Unal, 2017;Yang, 2017), grammar teaching (Al-Harbi & Alshumaimeri, 2016;Zainuddin & Halili, 2015), pronunciation (Yang & Chen, 2020), and vocabulary (Kang, 2015) as well as four basic skills; reading (Huang & Hong, 2016), listening (Roth & Suppasetseree, 2016), writing (Farah, 2014;Leis, Tohei & Cooke, 2015), and speaking (Wu, Hsieh & Yang, 2017). Also, some studies investigated the FCM's effect on learner autonomy (Han, 2015), student engagement and satisfaction (Alsowat, 2016), confidence (Mehring, 2015), motivation (Chen Hsieh, Wu & Marek, 2016), attitudes and perceptions (Prefume, 2015) in EFL classrooms.…”
Section: Introductionmentioning
confidence: 99%
“…Learners in flipped learning courses improved their language performance and communication skills (Lee & Wallace, 2017;Obari & Lambacher, 2015;Ishikawa et al, 2015), and increased linguistic and lexical understanding (Kang, 2015;Moranski & Kim, 2016;Leis, Cooke, & Tohei, 2015) when their pre-and post-test scores were measured and compared to non-flipped courses. Further, learners demonstrated high level of engagement during application of content concepts (Egbert, Herman, & Lee, 2015;Hung, 2015;Ishikawa et al, 2015), increased their motivation for completing language activities (Chen Hsieh, Wu, & Mark, 2016;Evseeva, & Solozhenko, 2015), had more flexible access to the content materials online (Ishikawa et al, 2015;Hernández Nanclares & Pérez Rodríguez, 2014), and acquired technological skills (Egbert et al, 2014). In particular, Moranski and Kim (2016) examined the impact of explicit grammar explanations of Spanish non-agentive se, given outside the classroom through video presentations, and guided practice, on a task-based class lesson.…”
Section: Introductionmentioning
confidence: 99%